1993
DOI: 10.1123/apaq.10.3.226
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Variables in Sprint Running of Athletes with Cerebral Palsy

Abstract: This paper describes the sprint running of selected Class 6, 7, and 8 international-level athletes with cerebral palsy (CP), contrasts their biomechanical characteristics with those reported for nondisabled runners, and delineates discriminating biomechanical parameters among classes. Subjects included 17 male and female Class 6, 7, and 8 athletes with CP who competed in international competition and were finalists or semifinalists in sprint events. High speed films were taken, and data reduction was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Athletes with CP usually show high rates of asymmetry during running ( Pope and Sherrill, 1993 ) but it is not clear its impact on performance. Exell et al (2012) , showed that asymmetry and running performance do not have a relationship in able-bodied athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Athletes with CP usually show high rates of asymmetry during running ( Pope and Sherrill, 1993 ) but it is not clear its impact on performance. Exell et al (2012) , showed that asymmetry and running performance do not have a relationship in able-bodied athletes.…”
Section: Discussionmentioning
confidence: 99%
“…Football players in class FT 7 have hemiplegia, with moderate hyperthonia and, finally, athletes in class FT 8 are minimally impaired and can be monoplegic, hemiplegic, or diplegic, with spasticity, athetosis, or both. 6,7 Football is considered an intermittent activity; the game takes place over an extended time period and is characterized by numerous short periods of high or maximum intensity exercise, interspersed with brief recovery periods. 8,9 Both aerobic and anaerobic energy systems must be activated to meet the energy demands of the muscles during play.…”
mentioning
confidence: 99%
“…13,24,25 Previous studies have described the anaerobic capacity in children, adolescents and adults with CP 17,18,26e28 and in athletes with CP. 6,29 However, despite the importance of anaerobic capacity in elite football performance, 30 and the necessity of knowing the anaerobic capacity of people with CP who practice this sport, 5 we are unaware of any study that assessed the anaerobic capacity of football players with CP. Such information would be useful to describe the anaerobic fitness of football players with CP and for population-specific training prescription.…”
mentioning
confidence: 99%
“…Skrotzky 44 showed that the decrease in stride length of children with cerebral palsy varied by the disability severity of children with cerebral palsy and the stride length became shorter when the effects of the neuromuscular system became larger. Pope et al 40 reported that the limit of step length in children with cerebral palsy was caused by the reduction of the hip exor, the decrease of pelvis rotation, and the increase of trunk exion angle. Sutherland et al 47 argued that cadence, step length, and stride length, spatiotemporal parameters, were the simplest and most perfect variables for analyzing gait and they were basic elements for examining mature gait.…”
Section: Discussionmentioning
confidence: 99%